OpenGL development cookbook : over 40 recipes to help you learn, understand, and implement modern OpenGL in your applications - Movania, Muhammad Mobeen (Packt Pub., 2013)
The book is written in a Cookbook format with practical recipes aimed at helping you exploit OpenGL to its full potential. This book is targeted towards intermediate OpenGL programmers. However, those who are new to OpenGL and know an alternate API like DirectX might also find these recipes useful to create OpenGL animations.